Domestic Violence among Married Women with Special Reference to Slums Areas of Karachi - Sarfaraz, Syeda Farhana (Advances in Social Sciences Research Journal, 2015)
Domestic violence is the most common form of gender-based violence. The declaration on the elimination of violence against women, adopted by the United Nation General Assembly in 1993 defines violence against women as “Any act of gender based violence that results, or is likely to result in physical, sexual or psychological harm or suffering to women, including threats of liberty, whether occurring in public or private life.” This research was conducted to know that what are the causes and situations which result in domestic violence, with special reference to slums areas of Karachi. In this study the researcher tried to focus on domestic violence on women’s by their husbands. In this study the researcher selected the slums area of North Karachi Town as universe and the married women of the slums area of North Karachi Town were the respondents. The researcher selected randomly 364 married women (respondents). The data is collected through the interviewing schedule.